Letter From the Editor: Into the Storm - David Axlyn McLeod (Journal of Forensic Social Work)
Thank you for joining us in this latest issue of the Journal of Forensic Social Work. We have some truly fantastic articles ahead; work that digs into the science of human behavior as it applies to complex systems and the practice of forensic social work. These are not just interesting academic explorations; they are urgent, they are necessary, and they are needed now more than ever. Our systems are under incredible strain, and as a profession, we are being called upon to find ways to use evidence as a mechanism to maintain the quality of life for people in an increasingly complex world. Research has never been more critical. Data-driven decision-making has never been more important.